Development of a Flipped Classroom-Based E-LKPD to Enhance Problem-Solving Skills in Particle Motion Dynamics - putrinabilajuniar puput; Fitri April Yanti; Iwan Setiawan (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2026)
he limited use of effective learning media in developing students’ problem-solving skills served as the basis for this study. This study focused on developing a flipped classroom-based e-LKPD on particle motion dynamics to enhance the problem-solving skills of 11th-grade students Research and development utilizing the ADDIE paradigm (Analysis, Design, Development, Implementation, Evaluation) was the research methodology used. A student response questionnaire and an expert validation questionnaire were among the tools utilized. Both quantitative and qualitative analysis were done. The created product is very appropriate for usage, as indicated by the average score of 91.94% in the product feasibility validation findings. The enhancement of pupils' ability to solve problems was classified as moderate, with an N-Gain value of 0.67, indicating that the use of flipped classroom-based e-LKPDs is effective in enhancing students’ problem-solving skills. Student The average score for the answer results was 86.40%, which is considered very excellent. The results of this investigation have the potential to promote student-centered learning and enhance problem-solving skills.